Ocean Acidification Affects Volatile Infochemicals Production and Perception in Fauna and Flora Associated With Posidonia oceanica (L.) Delile - Mutalipassi, Mirko; Mazzella, Valerio; Schott, Matthias; Fink, Patrick; Glaviano, Francesca; Porzio, Lucia; Lorenti, Maurizio; Buia, Maria Cristina; von Elert, Eric; Zupo, Valerio (Frontiers in Marine Science, 2022)
Communication among marine organisms is widely based on production, transmission, and interpretation of chemical cues. Volatile organic compounds can act as infochemicals, and ocean acidification can alter their production in source organisms as well as the interpretation of the information they drive to target organisms. Two diatoms (Cocconeis scutellum var. parva and Diploneis sp.) and a macroalga (Ulva prolifera), all common epiphytes of Posidonia oceanica leaves, were isolated and cultured at two pH conditions (8.2 and 7.7). Their biomass was collected, and the volatile organic compounds (VOCs) produced upon wounding were extracted and analysed using gas chromatography. Chemotactic reactions of invertebrates triggered by VOCs were tested using a static choice experimental arena and a flow-through flume system. Odour choice experiments were performed on several invertebrates associated with P. oceanica meadows to investigate the modification of behavioural responses due to the growth of algae in acidified environments. Complex patterns of behavioural responses were recorded after exposure to algal VOCs. This study demonstrated that a) ocean acidification alters the bouquet of VOCs released by diatoms and macroalgae and b) these compounds act as infochemicals producing peculiar behavioural responses in benthic invertebrates. In addition, these behavioural responses are species-specific, dose-dependent, and are influenced by the way odours reach target organisms (diffusion in static choice experimental arena vs active water movement in flow-through flume system). In conclusion, here we demonstrate that in future marine environments, higher CO2 concentrations (leading to a pH 7.7 in oceanic waters by the end of this century) can modify the production of VOCs by micro- and macroalgae and the recognition of these infochemicals by marine invertebrates.